Social Wellbeing, Board-Gender Diversity, and Financial Performance: Evidence From Chinese Fintech Companies - Ghafoor, Shahzad; Duffour, Kwame Asare; Khan, Uzair Farooq; Khan, Muhammad Kaleem (Frontiers in Psychology, 2022)
The study's main goal is to investigate the relationship between female representation on boards of directors and financial performance, using evidence from Chinese publicly traded companies which are providing financial services using cutting edge technologies. This research used fintech firms listed on the Shanghai (SH) and Shenzen Stock Exchange (SZ) from 2010 to 2019 to test the research questions using regression analyses by SPSS v26. According to the data, the Blau Index has a large and negative influence on Tobin's Q, demonstrating that gender diversity harms the performance of Chinese enterprises. Furthermore, CSR is found to have a significant and positive moderating influence on Tobin's Q, implying that the adoption of CSR converts from a negative to a positive effect. Diversified board members can improve the organization's control and monitoring operations, and female-represented boards of directors can participate in CSR activities that contribute to the organization's performance. The study contributes to the research of gender diversity by providing evidence that females on boards of directors enhance firm performance and the moderating function of CSR is examined with the link of female participation on boards of directors and financial performance